The association of Big-Five personality with co-rumination and its trade-off effect in Chinese adolescents: a cross-sectional study - Luo, Zilong; Luo, Pinchao (Frontiers in Psychology, 2025)
IntroductionCo-rumination, the excessive discussion of negative events with peers, exhibits a trade-off effect: it enhances friendship quality while simultaneously increasing the risk of internalizing problems in adolescents. Previous research has demonstrated group differences in this trade-off effect. Building on prior findings, this study explores the relationship between the Big Five personality traits and co-rumination among Chinese adolescents through three analytical components, aiming to identify at-risk groups for co-rumination using personality traits.MethodsThis cross-sectional study collected 765 valid self-reported responses. Measurement invariance of the Chinese version of the co-rumination questionnaire was examined, and latent variable structural equation models were constructed for each of the three research objectives to investigate the relationship between the Big Five traits and co-rumination.ResultsFirst, measurement invariance of the co-rumination questionnaire was assessed, revealing scalar invariance across gender and partial scalar invariance across age groups. Subsequent analyses examined the relationship between the Big Five traits and co-rumination. The first part showed that extraversion, neuroticism, and openness positively predicted co-rumination, while neuroticism explained gender differences in co-rumination. The second part confirmed the moderated trade-off effect of co-rumination; after controlling for the Big Five traits, the risk pathway of co-rumination became more robust, with gender differences observed in this pathway. The third part revealed distinct moderating effects of neuroticism, agreeableness, extraversion, and conscientiousness on the risk pathway.DiscussionGiven the measurement invariance results, the Chinese co-rumination questionnaire should be used more cautiously in studies involving multiple age groups. Structural equation modeling indicated that neuroticism serves as a strong indicator for identifying at-risk groups, as individuals with high neuroticism are more susceptible to risks associated with co-rumination. High conscientiousness and agreeableness were found to buffer against co-rumination-related depression and anxiety, respectively. The roles of openness and extraversion in relation to co-rumination appear more complex. Further research is needed to validate these findings.